Fun with English Activity for Elementary School Age Children At Naungan Kasih-Ende Orphanage - Pali, Agustina; Rando, Agnes Remi; Arafat, Siti (Universitas Negeri Makassar, 2024)
English language skills are one of the gateways to knowing the world globally. This indicates that learning English should be studied massively by various groups. However, not everyone has the same access to this experience. One of them is the children of the Naungan Kasih-Ende Orphanage. This community service activity aims to provide access to Basic English knowledge and skills to orphanage children who are beginner English language learners. This mentoring activity begins with teaching basic English (English for beginners). This activity was carried out for 2 months with an accompanying team consisting of 3 lecturers and 1 student. The partners in this activity were 11 elementary school age children at the Naungan Kasih Orphanage. The learning methods used in this activity vary, including games and songs, role play, drilling, total physical response with the aid of the learning media. The result of this activity is enthusiasm for learning English in a learning atmosphere without boring feeling. This pleasant learning atmosphere has a positive impact on improving participants' Basic English skills as measured by the test scores obtained at the end of the activity.